What Does a School Mean to a Community? Assessing the Social and Economic Benefits of Schools to Rural Villages in New York - Thomas A. Lyson (Journal of Research in Rural Education, 2002)
Using data from the 1990 U.S. Census andfrom the New York Stat.' Department of Education. I identify comm unitylevel characteristics associated with the presence or absence ofa school. My inquiry focuses on two sets ofrural communines: those with populations of500 or less and those with populations between 50 1 and 2.500. Ifind that the social and economic welfare in all rural communities is higher in places that have schools, Further. in the smallest villages. which haw.'fewer resources andfewe r civic places, schools are especially critical 10the social and economic well-being ofthe community. For pottcvmakers. educational administrators. and local citizens it is important to understand that schools are vital to rural communities. The mone y that might be saved through consolidation could be forfeited in lost taxes, declining property values. and los/ businesses.